Unjuk Kerja Pengembangan Prototype Alat Pengering Padi Metode Thin Layer - Abdi Musyafiq, Afrizal; Dewi, Riyani Prima; Purwiyanto, Purwiyanto; Subarkah, Rafiq (P3M Politeknik Negeri Cilacap, 2023)
Based on data from the Central Statistics Agency (BPS) for 2019, Cilacap Regency has an area of 14,000 hectares of rice farming land with a potential for harvesting up to 920,000 tons of rice, then the Binangun District area has 66.5 hectares of rice farming land with a potential of harvesting up to 32,000 tons of rice. Turning paddy into rice requires many processes, one of which is drying rice. Traditional rice drying takes a relatively long time, has an uneven moisture content, and is under an unstable temperature therefore it is necessary to develop a thin-layer method for drying rice. This study used the Rex C100 Thermocontrol as a drying temperature controller, used an Arduino Uno equipped with a BTS 7960 driver to adjust the stirring speed, and a YL-69 sensor to read the rice moisture content. Tests in this study were carried out using Inpari-32 rice with a mass of 2 Kg and a drying temperature of 50-80oC. The result of this study was that the relationship between temperature and time in drying was inversely proportional. The rice drying process uses the highest drying power of 654.5 watts while the lowest power is 467.5 watts. The lowest overall energy use was 2.05 x106 J and the highest energy was 2.60 x106 J. The highest drying rate was 0.50%bk/minute. Effective drying uses a temperature of 80oC with a time of 30 minutes to reach the store-dry rice and 70 minutes to reach the dry milled rice category.